ANALISIS WAVELET DAN VARIABILITAS TEMPORAL HIDROKLIMATOLOGI DAERAH ALIRAN SUNGAI (STUDI KASUS SUB-DAS CISANGKUY KABUPATEN BANDUNG) - Dadang Subarna; M Yanuar J Purwanto; Kukuh Murtilaksono; Wiweka Wiweka (Fakultas Perikanan dan Kelautan, Universitas Riau, 2012)
The research was conducted in the Sub Watershed Cisangkuy of theUpper Citarum Watershed in the Bandung regency. Cisangkuy river playsimportant role in the water supply to the population of Bandung regency andBandung city. In the last ten years, the debit of the river was decreased at dryseason but increased at rainy season that causes of flood in some places. It isneeded to research the variability of hydroclimatology at the region. The monthlyrainfall and debit in range of 2001-2011 was processed using the coefficient ofvariation (CV), wavelets and moving average analysis. The result of thecoefficient of variation and wavelets analysis show the monthly rainfall of fourweather stations: Cileunca, Kertamanah, Cipanas and Ciherang have the CV of78%, 82%, 84%, 70% respectively and show the dominant oscillation around 8-16months. The debit of two hydrology stations: Pataruman and Kamasan have theCV of 97%, 86% respectively and show the dominant oscillation around 128months and 64 months. The analysis of moving average with the simple,exponential, adaptive methods show the increase of five yearly debit significantlyin the range of observed data which cause of the flood in the Kamasan Banjaranregion. The 8-16 months oscillation is associated with the apparent position of theSun between the Tropics of Cancer and Capricorn which cause regional variationsin the intensity of monsoon and it’s called annual oscillation. The 128 monthsoscillation of debit is associated with the ten to twelve (TTO) years oscillation inthe tropical tropospheric temperature. While 64 months oscillation is associatedwith the the tropical Pacific phenomena El Niño (warm condition) and La Niña(cold conditions) are the cause of 2-7 years oscillations which famous with ENSOcycle.Keywords: Watershed, Rainfall, Debit, Variability, Hidroclimatology, Wavelets,Moving Average, Oscillation